A Truly Missed Opportunity: The Political Context and Impact of the Basic Income Experiment in Finland. Issue 3 (September 2022) - Hiilamo, Heikki
Finland conducted the first nationwide field experiment with partial basic income between 2017 and 2018. The experiment and its results were widely reported in international media and featured in political debates across the globe. Domestically, the experiment had an impact on social policy debates but no impact on social policy. For example, it did not feature in the Social Security 2030 project or in the work of the Social Security Reform Committee (2020–2027). The research setting for the experiment was compromised from the beginning due to political reasons; but the scientific power was further undermined by a new sanctioning model, which was implemented in 2018 at the beginning of the second year of the basic income experiment. The new Government taking office in 2019 promised to continue with a negative income tax experiment; however, no such experiment was conducted. The article will unpack these developments in Finland and discuss possible explanations for denouncing basic income as a policy idea.